To the knowledge of the fauna of thrips (Thysanoptera) of the Middle East and the South Caspian region - S.V. Poushkova (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
Various thrips materials in different regions of the Middle East and the Caspian region have been collected. New data on the fauna of the region are given. Fifteen species are reported for Lebanon for the first time: Aeolothrips collaris, Melanthrips knechteli, Thrips australis, Th. hawaiiensis, Th. major, Th. mediterraneus, Th. mareoticus, Frankliniella occidentalis, Limothrips transcaucasicus, Odontothrips phaleratus, Compsothrips albosignatus, Bacillothrips nobilis, Haplothrips leucanthemi, H. minutus, H. vuilleti. Nine species, Aeolothrips intermedius, Rhipidothrips elegans, Melanthrips fuscus, Thrips physapus, Limothrips transcaucasicus, Dendrothrips saltator, Neohydatothrips abnormis, Haplothrips aculeatus, H. tritici, are recorded for Azerbaijan for the first time. One unidentified species of (?) Aeolothrips was collected in Western Iran, images of this species are given.